Peran Brand Image dan Harga dalam Meningkatkan Keputusan Pembelian - Sulistyawati, Ni Kadek; Hartati, Putu Sri; Dewi, Ida Ayu Sasmita (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The purchase decision is the act of consumers making a purchase of a product or service offered by the store. The purpose of this study was to determine the effect of brand image and price on purchasing decisions of Roman ceramics. This research was conducted at UD. Rukun Makmur which is located on Jalan Gatot Subroto Barat. The number of respondents taken as many as 55 respondents with accidental sampling method. Data was collected by means of a questionnaire. The data analysis technique used to answer the hypothesis is multiple linear regression consisting of determination test, t test (partial regression), and F test (simultaneous regression). Based on the results of the study, it can be seen that brand image has a positive and significant effect on purchasing decisions and price has a positive and significant effect on purchasing decisions for Roman brand ceramics at UD. Rukun Makmur Gatsu Barat Denpasar. Suggestions that can be given to this researcher is UD. Rukun Makmur provides complete information about Roman brand Ceramic products to all buyers.